Comparative Antennal Morphology of Agriotes (Coleoptera: Elateridae), with Special Reference to the Typology and Possible Functions of Sensilla - Faucheux, Michel J; Németh, Tamás; Kundrata, Robin (Insects, 2020)
Species of the click-beetle genus Agriotes Eschscholtz are economically important crop pests distributed mainly in the Northern Hemisphere. They can inflict considerable damage on various field crops. Therefore, the detection, monitoring, and control of Agriotes include the adult trapping using species-specific sex pheromones, which is a critical component of pest research. To obtain a better understanding of the detailed antennal morphology as background information for subsequent chemical ecology research, we conducted a scanning electron microscopy study of the antennal sensilla of both sexes in 10 European Agriotes species. We identified 16 different sensilla in Agriotes, belonging to six main types: sensilla chaetica (subtypes C1 and C2), sensilla trichodea, sensilla basiconica (subtypes B1-B9), dome-shaped sensilla (subtypes D1 and D2), sensilla campaniformia, and Böhm sensilla. We discuss their possible functions and compare the sensilla of Agriotes with those of other Elateridae in order to consolidate the sensillum nomenclature in this family. Additionally, our study reveals the remarkable interspecific variability in sensillar equipment of Agriotes and identifies several characters of potential importance for future use in systematic studies. The present study provides a strong preliminary framework for subsequent research on the antennal morphology of this crop pest on a wider scale.
Keywords: crop pest; chemoreceptors; pest control; click-beetles; wireworm; scanning electron microscopy; pheromones